Herbie Hancock and the Rockit Band - Hancock, Herbie, 1940-; Media Lab Ltd.; CBS Fox Video (Farmington Hills, MI : CBS/FOX Video, 1984)
A multi-media presentation featuring robots, break dancers, and a spectacular light show that adds up to a visual extravaganza. As an extra bonus, the award winning music videos "Rockit" and "Autodrive."
VHS format.
"VHS 6619"
Performed live at the Hammersmith Odeon and Camden Palace in London, England.
Director, Ken O'Neil ; producer, Lexy Godfrey ; executive producer, David Rubinson.
Herbie Hancock, The Rockit Band: D.ST., Bernard Fowler, Wayne Brathwaite, Anton Fier, J.T. Lewis, Jeff Boyd.
Keywords: Concerts; Rock music